Talk with your hands, listen with your eyes - Ellerbusch, Kristin; Mitchell, Anastasia ([Mankato, MN] : Child's World, 1993)
Instructions for talking with American sign language, beginning with the alphabet and then presenting basic useful vocabulary.
Keywords: American Sign Language -- Juvenile literature; Finger spelling -- Juvenile literature; Sign language